The Figurative Language in Niki Zefanya Songs Lyrics - Andi Intan; Suleman Bouti; Jefriyanto Saud (Transbahasa, 2025)
The purpose of this research is to identify and analyze the use of figurative language in the song lyrics of Niki Zefanya. This study focuses on five selected songs: La La Lost You, Lowkey, Every Summertime, High School in Jakarta, and I Like U. Using a qualitative descriptive method with a library research approach, data were collected through intensive reading of relevant literature and the lyrics of the selected songs. The analysis process was carried out in three stages: identification, classification, and interpretation of the figurative language found in the lyrics. This research applies the theory of figurative language proposed by Kennedy and Gioia (2007), which includes various types such as metaphor, personification, hyperbole, and symbolism. The findings reveal that Niki Zefanya frequently uses figurative language to express emotions and enhance the artistic quality of her lyrics. Specifically, the study found four instances of metaphor, two instances of personification, five instances of hyperbole, and two instances of symbolism. These figurative expressions contribute significantly to the depth and aesthetic value of her songwriting. This study highlights the richness of language in contemporary music and provides insight into literary devices in pop culture.